Public space: ideal concept of a state in Colombia (2015)
The purpose of this test is to show how the creation of standards by the Colombian State works as an instrument to bring asymmetric positions, emphasizing economic issues as the linchpin of both positions. For development, the topic will be approached from different stages. Initially, the individual characteristics of the agents involved in the public space is considered. Then in the second stage, they will present some of the international and national strategies are in place to regulate the use of public space.